2017
DOI: 10.1097/bot.0000000000000737
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varying Tension of a Suture Button Construct in Fixation of the Tibiofibular Syndesmosis—Evaluation Using Stress Computed Tomography

Abstract: Suture button constructs must be appropriately tensioned to maintain reduction and re-approximate the degree of physiological motion at the distal tibiofibular joint. These constructs also demonstrate overcompression of the syndesmosis; however, the clinical effect of this remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Previous studies have shown increased posterior translation of the fibula with SB constructs compared to screw constructs, 6 and excessive sagittal plane motion has remained a primary concern with the use of SB in syndesmosis repair. 17,21,26,33,34 This study demonstrates a lack of excessive sagittal plane motion under simulated physiologic, lower torque conditions in an isolated syndesmotic injury model.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown increased posterior translation of the fibula with SB constructs compared to screw constructs, 6 and excessive sagittal plane motion has remained a primary concern with the use of SB in syndesmosis repair. 17,21,26,33,34 This study demonstrates a lack of excessive sagittal plane motion under simulated physiologic, lower torque conditions in an isolated syndesmotic injury model.…”
Section: Discussionmentioning
confidence: 64%
“…Overcompression of the syndesmosis has been demonstrated in multiple cadaveric studies, 16,39,40 as well as in vivo. 41 This is facilitated by the large mechanical advantage produced by the reduction forceps, especially when larger pelvic reduction forceps are utilized.…”
Section: Discussionmentioning
confidence: 94%
“…O uso de TC vem se destacando em vários estudos como os de Fitzpatrick et al (11) , Morellato et al (12) e Elgafy et al (13) , os quais demonstraram que a análise de tomografias computadorizadas é um fator importante para verificação de resultados ineficientes na redução e estabilização de uma lesão da sindesmose.…”
Section: Discussionunclassified